In vitro evaluation of the amoebicidal activity of rosemary (Rosmarinus officinalis L.) and cloves (Syzygium aromaticum L. Merr. & Perry) essential oils against Acanthamoeba polyphaga trophozoites. Issue 4 (16th February 2019) - Anacarso, Immacolata; Sabia, Carla; de Niederhäusern, Simona; Iseppi, Ramona; Condò, Carla; Bondi, Moreno; Messi, Patrizia
Abstract: Several species of the genus Acanthamoeba cause human diseases. Treatment of infections involves various problems, emphasising the need to develop alternative antiprotozoal agents. We studied the anti-amoebic activity of Essential Oils (EOs), derived from rosemary ( Rosmarinus officinalis L.) and cloves ( Syzygium aromaticum L. Merr. & Perry), against Acanthamoeba polyphaga strain. The amoebicidal activity of cloves and rosemary EOs was preliminary demonstrated by the morphology change (modifications in the cell shape, the presence of precipitates in the cytoplasm, autophagic vesicles, membrane blends) of the treated trophozoites. The cell-counts, carried out after staining trophozoites with a Trypan blue solution, revealed that both EOs were active in a dose-dependent manner and in relation to the exposure time. This activity was evident after few hours, with encouraging results obtained in particular with cloves EO, able to act at the lower concentrations and after 1 h, probably for its high eugenol content (65.30%). Abstract :